Estudo das propriedades ópticas de pós cerâmicos à base de Zn3Ga2Ge2O10: X% Cr3+ (X = 0 ; 0,5 ; 0,75 ; 1,0) - Zanini, Tatiana Salvetti [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Ceramic powders based on Zn3Ga2Ge2O10: Cr3+ X% (X = 0.0; 0.5; 0.75; 1.0) were synthesized by solid-state reaction method. The gallium-zinc germanate doped with chromium presents an interesting property of phosphorescence, that means, it is capable of emitting light when excited by a source of radiation, and such emission remains for some time after stopping the source. For this reason, these materials can be widely applied in night-vision surveillance, (through the use of solar energy, for example), electronic devices screen, emergency routes signals, control panels indicators in dark environments, etc. In this job were considered different amounts of dopant in order to perform a comparison of structural and photoluminescent properties. For that, some analyses were performed on samples, such as XRD, FT-Raman, SEM, UV-vis and photoluminescence measurements (PL). Such analysis allowed to infer that the presence of chromium results in no phase transformation, so that the four compositions have the same set of phases: cubic, rhombohedral and hexagonal. Although the structure was not changed, chromium influences other properties / characteristics of these materials. Examples are: increase of band-gap, decrease of average particle size, small changes in binding energy checked by Raman and especially the increase of photoluminescent property. The chromium ions have great ease in replacing gallium ions in octahedral sites, resulting in emission of light with a wavelength of about 700 nm (infrared region), which is justified by the spin-forbidden 2E 4A2 transition. In other words, chromium is a favorable luminescent center, acting as a trap in the crystal structure, since it imprisons the excitation energy easily and releases it gradually, allowing the phosphorescence. It was observed that the composition ... (Complete abastract click electronic access below)

Foram sinterizados, por reação em estado sólido, pós cerâmicos à base de Zn3Ga2Ge2O10: X% Cr3+ (X=0,0; 0,5; 0,75; 1,0). O germanato de gálio-zinco dopado com cromo apresenta propriedade fotoluminescente de fosforescência, ou seja, é capaz de emitir luz quando excitado por alguma fonte de radiação, sendo que essa emissão permanece por certo tempo após a interrupção da fonte. Por essa razão, esses materiais podem ser amplamente aplicados em iluminação noturna para vigilância, (mediante a utilização de energia solar, por exemplo), tela de dispositivos eletrônicos, sinais de rotas de emergência, indicadores de controle de painéis em ambientes escuros, entre outros. Neste trabalho, foram utilizadas diferentes adições de Cr3+ com o objetivo de realizar uma comparação das propriedades estruturais e fotoluminescentes. Para tanto, foram realizadas algumas análises nas amostras dos pós, como DRX, Raman, MEV, UV-vis e medidas de fotoluminescência (FL). Apesar de não alterar a estrutura, o cromo exerce influência em outras propriedades/características dos pós. Exemplos disso são: o aumento do band-gap, a diminuição do tamanho médio de partículas, pequenas alterações na energia de ligação verificadas pelo Raman e, principalmente, aumento da propriedade fotoluminescente. Os íons cromo possuem grande facilidade em substituir os íons gálio em sítios octaedrais, dando origem à emissão de luz com comprimento de onda de aproximadamente 700nm (ou seja, região do infravermelho), devido à transição proibida de spin 2E 4A2, característica de campo cristalino forte. O cromo é um centro luminescente favorável, atuando como armadilha na rede cristalina, uma vez que aprisiona a energia de excitação com facilidade e a libera gradualmente, permitindo a fosforescência ... (Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Ceramica (Tecnologia); Fotoluminescencia; Germanio - Isotopos; Cromo; Photoluminescence